Mirror Therapy Rehabilitation for Lower Limb of Acute Stroke Patients - Limtrakarn, Wiroj; Tangmanee, Noppamad; Muengtaweepongsa, Sombat (Applied Science and Engineering Progress, 2022)
This paper aims to study the effectiveness of mirror therapy (MT) for treatment of acute stroke patients. The subjects of 20 acute stroke patients who possessed the ability to respond to verbal instructions were randomly blinded and allocated to a control group (n = 10, 59.2 ± 2.28 years) and a mirror group (n = 10, 53.8 ± 6.14 years). Both groups were treated by intervention of traditional rehabilitation therapy and compared with MT. The intervention of MT was taken 60 minutes per day, 5 days per week for 12 weeks. Measures of intervention effectiveness were taken before treatment and after treatment by therapist using Brunnstrom stages, Fugl-Meyer Assessment (FMA) lower extremity score, and Brunnel Balance Assessment (BBA) balance. Data were analyzed using an independent sample t-test. The results revealed that, after 12 weeks of treatment, subjects of both groups gained statistically significant improvements in all measured variables (p < 0.05). The participants of the MT group had improvement on the FMA score (31.0 ± 1.20 versus 28.7 ± 0.58) compared with the control group. MT is inexpensive and easily applicable in conjunction with traditional physiotherapy for home care programs. Consequently, MT proves to be an effective approach for rehabilitation of patients with post-acute stroke.